Integration of Islamic Religious Education, Al Quran Science and General School Subjects at Adzkia Babalan Integrated Islamic Junior High School, Langkat Regency - Atika, Nur; Salminawati, S; Dahlan, Zaini (Universitas Muhammadiyah Surakarta, 2025)
This research is motivated by the dichotomy of Islamic Religious Education with general learning in junior secondary education in Integrated Islamic schools which today are increasingly seen in the world of education, especially Islamic education. The method used in this study is qualitative phenomenology. The collection method was carried out by observation, documentation, and interviews. To obtain the validity of the data, it is tested with validity and data analysis which includes data reduction, data presentation and conclusion drawn. The planning guide is a combination of the official curriculum and the JSIT curriculum consisting of the Independent and INTEGRATED Curriculum Learning Implementation Plan (Exploratory Study, Formulate, Presentation, Apply Duniawi Ukhrawi). The implementation of learning integration is in the classroom delivered by general subject teachers to provide understanding and awareness to students about the learning integration materials of PAI, Qur'an and General Sciences. This integration is synergized in supporting programs such as masta (student ta'aruf period), mabit (night of faith and taqwa development), dauroh (training), BPI (Islamic Personal Development), worship habituation. The analysis method in this paper adopts the basic principles of value education in Islam, namely monotheism, science and morals, which is based on the scientific integration between general science and religious science (non-dichotomous). The integration of Islamic values in general subjects is manifested in the learning pattern of PAI and Qur'an Science which comprehensively (integral-holistic) respects the existence of general subjects as general sciences and Islamic studies as religious sciences while responding to the needs of society and families. In its implementation, the learning heeds the values of monotheism, stimulates the continuous search for knowledge and pays attention to the moral and noble aspects of students.